Accessibility to health services in Italy and in the world. (30th September 2020) - Marchetti, G; Simonelli, M; Dente, M G; Marceca, M; Declich, S
Abstract: Background: The Universal Health Coverage (UHC) proposes that an ideal health system must be able to extend the health coverage to the whole population (universality), to guarantee all the necessary services (globality) and to do it without additional direct costs for the people (free of charge). The achievement of the UHC represents the target 3.8 of the Sustainable Developed Goals. The World Health Organization and the World Bank have developed an index to monitor the UHC (an algorithm that contains 16 indicators of essential health services), while for financial protection they rely on the incidence of catastrophic expenditure on health (percentage of families in which the living expenses for health without reimbursement exceed the10% of consumption). Objectives: To strengthen the Italian operators' knowledge about the accessibility to health services in Italy and in countries around the world utilizing the UHC index and the incidence of catastrophic expenditure. Results: The National Center for Global Health of the Italian National Institute of Health (ISS) collected the documents and the data already produced and validated by the international scientific community. ISS in collaboration with the Department of Public Health and Infectious Disease of Sapienza University of Rome developed a workshop training program to bring the UHC concepts at national level in a simplified manner. This was developed in order to encourage a reflection and to strengthen the understanding of the complexity of the UHC. The framework and the program of the workshop will be presented during the conference. Conclusions: Studying the UHC means focusing on the inequalities in health care. To increase the sensibility of professionals may be a resource to promote the health coverage for all in the national territory. Key messages: Encouraging the discussion between professionals is possible to understand the complexity of the UHC. The achievement of the UHC may happen only through the improving of the knowledge about it.